2006
DOI: 10.1016/s1672-0229(06)60011-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Nuclear Matrix Proteins Following the Differentiation of Human Osteosarcoma MG-63 Cells

Abstract: Human osteosarcoma MG-63 cells were induced into differentiation by 5 mmol/L hexamethylene bisacetamide (HMBA). Their nuclear matrix proteins (NMPs) were selectively extracted and subjected to two-dimensional gel electrophoresis analysis. The results of protein patterns were analyzed by Melanie software. The spots of differentially expressed NMPs were excised and subjected to in situ digestion with trypsin. The maps of peptide mass fingerprinting were obtained by MALDI-TOF-MS analysis, and were submitted for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Previous studies in other cell lines showed that the composition of the nuclear matrix varies during the different stages of cell differentiation [Zhao and Li, 2005]. Similarly, our own studies confirmed that the HMBAinduced differentiation of the human osteosarcoma cell line MG-63 was accompanied by changes of NMPs [Zhao et al, 2006a]. In the present study, we show for the first time that the levels of specific NMPs change during the differentiation of SK-N-SH cells.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies in other cell lines showed that the composition of the nuclear matrix varies during the different stages of cell differentiation [Zhao and Li, 2005]. Similarly, our own studies confirmed that the HMBAinduced differentiation of the human osteosarcoma cell line MG-63 was accompanied by changes of NMPs [Zhao et al, 2006a]. In the present study, we show for the first time that the levels of specific NMPs change during the differentiation of SK-N-SH cells.…”
Section: Discussionsupporting
confidence: 89%
“…Previous researches showed that the composition of nuclear matrix in other cell lines varied apparently in the different stages of cell differentiation [20,21] . Our early studies also confirmed that the induced differentiation of human osteosarcoma cell line MG-63 and human gastric adenocarcinoma cell line MGC80-3 with HMBA was accompanied with changes of nuclear matrix proteins [13] . In this study, we proved for the first time that specific nuclear matrix proteins were accompanied with the differentiation of SMMC-7721 cells.…”
Section: Smmc-7721supporting
confidence: 75%
“…The nuclear matrix in cancer cells is not only abnor mal in morpholog y, but also apparently different in its composition [11] . Our early studies showed distinct changes of the morphology or protein composition of nuclear matrix during differentiation of several cell lines treated with different reagents [12,13] . It is implied that those differentially expressed nuclear matrix proteins not only have direct association with regulators of cell cycle and signal transduction, but also are important during the cancerization and its reversion of the cell.…”
Section: Introductionmentioning
confidence: 92%
“…The native protein pattern in the nuclear matrix varies in a tissue-specific manner and change as cells differentiate (Zhao et al, 2006). Structural and functional components of the nuclear matrix are targets for the alkylating chemotherapeutic agents mainly the CYP that interacts with proteins of the nuclear matrix and with DNA close to transcription sites and matrix-bound replication ( Fernandes and Catapano, 1995;Muenchen and Pienta, 1999).…”
Section: Introductionmentioning
confidence: 99%